Communication of Organizations in Organizations Change’s Phenomenon in Research and Development Institution - Romadona, Mia Rahma; Setiawan, Sigit (Jurnal Pekommas, 2020)
When the change has become a necessity for organizational life and it is important to increase the productivity and role of research institutions, it must be done. Change as a necessity needs to be pursued and carried out with a mature strategy to be able to minimize resistance and material and immaterial costs. The immaterial aspect that plays a very important role and as a key is an organizational communication that needs to be prepared as a strategy that can have an extraordinary influence on the success of the organizational change. But what about when these changes are not optimally communicated? The purpose of this study is to examine the dynamics of the phenomenon of organizational communication dynamics in a research institution that carries out organizational change. This research has benefits because it can provide a critical picture and analysis of organizational change in terms of organizational communication dynamics in research institutions. This research method uses a qualitative phenomenological approach to capture the image meaning of a series of events in the process of organizational change in research institutions from the aspect of organizational communication. The phenomenon of organizational change began with various rejections from various levels of employees both researchers and non-researchers who demanded openness and certainty and maintain the honor of the institution as a research institution. The demand for information disclosure is a reflection of the inability of the organization's management to communicate the planned change strategy to cause resistance to the process.